Atrial fibrillation with hemodynamic instability after the use of the third dose of adenosine during surgery for 7 intracranial aneurysms: case report - Quiroz-Murga, Eduardo; Simon-Scamarone, Grassy (Colombian Journal of Anesthesiology, 2019)
Adenosine-induced asystole is a technique that prevents and controls the intraoperative rupture of cerebral aneurysm, facilitating temporary, and/or definitive clipping of the aneurysm. This is the case of a 58-year-old woman who underwent clipping of 7 intracranial aneurysms, who was induced asystole with adeno-sine 3 times and developed atrial fibrillation with hemodynamic instability after the last dose. Adenosine has been shown to be useful and safe, however, its use should be planned and possible cardiological complications should be considered.